Assessment of Fashion Aesthetic Knowledge among Fashion Design Students: A Study on Educational Measurement - Fortuna, Fadhilah Prilia; Prabawati, Melly; Arrsyi, Esty Nurbaity (LPPM Universitas Negeri Jakarta, 2025)
This study aims to assess students' Knowledge of fashion aesthetics through a structured cognitive measurement approach grounded in educational assessment theory. The research focuses on three cognitive domains: understanding (C2), application (C3), and analysis (C4), based on the revised Bloom's taxonomy. A test instrument consisting of 40 true-false items was developed and validated by experts in fashion aesthetics and educational Measurement. The research involved 135 students from the Fashion Design Education Program at Universitas Negeri Jakarta, selected using a multistage random sampling technique from a population of 226 students. The results showed that 106 students demonstrated adequate understanding (C2), 85 students were able to apply the Knowledge (C3), and only 34 students were capable of performing analytical tasks (C4). These findings indicate a strong foundation at the lower cognitive levels but a significant gap in higher-order thinking skills. The study highlights the importance of valid, domain-specific assessment instruments in vocational education and emphasizes the need for instructional strategies that promote deeper conceptual engagement, application in authentic contexts, and critical analysis. The results also suggest a need for curriculum redesign that integrates process-oriented and authentic assessments to prepare students for decision-making in aesthetic contexts.